DAMPAK KELEMAHAN KEPEMIMPINAN KEPALA SEKOLAH DAN ETOS KERJA GURU SD NEGERI 173629 SIMANALESE: TINJAUAN KASUS BERBASIS PERSPEKTIF MANAJEMEN PENDIDIKAN - Midaniati Pane; Elisamark Sitopu; Elsina Sihombing (STKIP Subang, 2026)
This study aims to analyze the principal’s leadership practices in responding to the decline in teachers’ work ethic, describe the dynamics of teachers’ work behavior, and examine the impact of weak leadership and declining teacher work ethic on school operations and the quality of learning services at SD Negeri 173629 Simanalese. The study was motivated by recurring issues of teacher tardiness, low compliance with instructional administration, limited participation in school organizational activities, and the ineffective implementation of teacher supervision and development programs by the principal. This research employed a qualitative approach using a case study design. Data were collected through observations, in-depth interviews, and documentation involving the principal and teachers as research informants. Data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. Data trustworthiness was ensured through source triangulation and technique triangulation. The findings revealed that the principal had implemented various supervisory and developmental efforts through verbal warnings, written reprimands, coordination meetings, and personal approaches. However, these efforts had not succeeded in producing consistent and sustainable behavioral changes among teachers. The dynamics of teachers’ work ethic were reflected in poor time discipline, inadequate completion of instructional administration, and low participation in school organizational activities. These conditions were influenced by internal factors, such as declining work motivation and job fatigue, as well as external factors, including weak organizational culture, ineffective supervision, and inconsistent enforcement of school regulations. Consequently, these conditions disrupted the learning process, reduced students’ learning time, weakened school coordination, and lowered the quality of educational services. This study concludes that strengthening principal leadership, implementing continuous teacher development, and fostering a disciplined and responsible organizational culture are essential for improving educational quality at SD Negeri 173629 Simanalese.